The Role of Strategic Agility in Organizational Sustainability: An Analytical Study of the Opinions of a Sample of Faculty Members in Private Universities in Erbil (Raparin Journal of Humanities (RJH), 2026)
The objective of this research is to investigate how strategic agility, as embodied by its three dimensions (opportunity exploration, opportunity exploitation, and structural agility) can support organizational sustainability, which is mirrored in its economic, social, and environmental dimensions. The research issue stems from the inadequate comprehension and implementation of strategic agility and its role in attaining organizational sustainability in Erbil's private universities. The study's entire framework is centered on determining the central research topic, which poses important queries regarding the nature of the connection and its consequences between organizational sustainability and strategic agility. A conceptual model created to answer these concerns, and it has two hypotheses that have been examined using the proper statistical methods. Using a pre-made questionnaire, the study collected primary data using a descriptive analytical methodology. All of the faculty members from eight carefully chosen private universities in Erbil made up the study population. 375 of the 410 surveys that were sent were returned, and 356 of those were judged suitable for statistical examination. To evaluate the suggested hypotheses, data were analyzed using AMOS (Version 24) and SPSS (Version 24). At both the overall and dimensional levels, the statistical findings showed important effects and significant positive correlations between organizational sustainability and strategic agility. The study suggests implementing strategic agility as a crucial strategic technique to improve organizational sustainability in private colleges in light of these findings.